Retrospective Attention Interacts with Stimulus Strength to Shape Working Memory Performance. - Theresa Wildegger; Glyn Humphreys; Anna C Nobre (PLoS ONE)
Orienting attention retrospectively to selective contents in working memory (WM) influences performance. A separate line of research has shown that stimulus strength shapes perceptual representations. There is little research on how stimulus strength during encoding shapes WM performance, and how effects of retrospective orienting might vary with changes in stimulus strength. We explore these questions in three experiments using a continuous-recall WM task. In Experiment 1 we show that benefits of cueing spatial attention retrospectively during WM maintenance (retrocueing) varies according to stimulus contrast during encoding. Retrocueing effects emerge for supraliminal but not sub-threshold stimuli. However, once stimuli are supraliminal, performance is no longer influenced by stimulus contrast. In Experiments 2 and 3 we used a mixture-model approach to examine how different sources of error in WM are affected by contrast and retrocueing. For high-contrast stimuli (Experiment 2), retrocues increased the precision of successfully remembered items. For low-contrast stimuli (Experiment 3), retrocues decreased the probability of mistaking a target with distracters. These results suggest that the processes by which retrospective attentional orienting shape WM performance are dependent on the quality of WM representations, which in turn depends on stimulus strength during encoding.